Fishery data collection systems for Eastern Caribbean islands : proceedings - Mahon, Robin, ed. (OECS Cane GardenVC, 1988)
Contains four papers which discuss data collection systems for eastern Caribbean Islands. Outlines the structure and function of the OECS fishery database; species and species groupings in Eastern Caribbean Islands and units of fishing effort in Eastern Caribbean fisheries. Compiles information on the fisheries of eastern Caribbean CARICOM member states, Anguilla and the British Virgin Islands, relevant to designing a data collection system and provides a preliminary description of such a system for each territory.